Respuesta :

51894

Answer:

Step-by-step explanation:

for the first point (0, -5) let’s say 0 = X1 and -5 = Y1

for the second point (-3, 4) let’s say -3 = X2 and 4 = Y2

to find m (the slope) we set this up:

(4-(-5))/(-3-0)

9/-3

slope is -3

what we have for the equation so far is

y = -3x + b

we have two points that the line has to go thru and to find b we’ll plug in one of those points into the equation

let’s use (0, -5)

-5 = -3(0) + b

-5 = 0 + b

b = -5

**if you used the other point b will still be -5

when we plug b back into the equation we get

y = -3x -5

hope this helps

ACCESS MORE